1967
DOI: 10.2337/diab.16.5.336
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Periodontal Disease

Abstract: tudies of the relationship between periodontal disease and certain systemic disorders have shown that a positive association may exist. As part of the celebration of the completion of phase I of the new Dental Clinics and research addition at the School of Dentistry, the University of Western Ontario, and to increase public and professional understanding in this specific field, a state-of-the-science symposium entitled "Periodontal Health and Systemic Disorders" was held on September 27, 2001, in London, Ontar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1
3

Year Published

1970
1970
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 0 publications
0
46
1
3
Order By: Relevance
“…Those patients in the 'inconclusive group' had lost their teeth almost completely, probably because of severe periodontitis and/or caries. While a high incidence of periodontitis has been noted in diabet ics [4], and it was shown that the degree of periodontal disorders was significantly correlated with age, variance of blood sugar, and duration of diabetes [4], no signifi cant differences were noted in the period of diabetes, blood glucose level, or hemoglobin A in the present investigation. Other parameters which are related to par athyroid function did not show significant differences between the inconclusive and conclusive groups.…”
Section: Discussioncontrasting
confidence: 38%
“…Those patients in the 'inconclusive group' had lost their teeth almost completely, probably because of severe periodontitis and/or caries. While a high incidence of periodontitis has been noted in diabet ics [4], and it was shown that the degree of periodontal disorders was significantly correlated with age, variance of blood sugar, and duration of diabetes [4], no signifi cant differences were noted in the period of diabetes, blood glucose level, or hemoglobin A in the present investigation. Other parameters which are related to par athyroid function did not show significant differences between the inconclusive and conclusive groups.…”
Section: Discussioncontrasting
confidence: 38%
“…The treatment of periodontal disease is to prevent progression of the disease and to preserve the dentition. This was not a new idea, but had been proposed by Finestone and Boorujy in 1967 [88].…”
Section: Diabetes and Periodontitismentioning
confidence: 93%
“…The relationship between diabetes mellitus and periodontal disease has been studied extensively, but the interpretation of the results is complicated by findings that the prevalence of both diseases increases with age, and that well-controlled diabetics may not exhibit more gingivitis or destructive periodontitis than non-diabetics (Finestone and Boorujy, 1967;Sznajder et al, 1978). As a result, some studies have failed to confirm the relationship between diabetes and periodontal disease (Mackenzie and Millard, 1963;Beneviste et al, 1967;Hove and Stallard, 1970;Tenovuo et al, 1986), while other investigators have supported it through their findings (Belting et al, 1964;Sznajder et al, 1978;Cianciola et al, 1982).…”
Section: Introductionmentioning
confidence: 93%